A Teacher's Reflection on the Implementation of Project-Based Learning to Enhance Speaking Skills in Grade 6 Elementary Students - -, Rukadah -; Rukadah, Rukadah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This qualitative case study investigates the reflective practices of an English teacher with 20 years of experience, focusing on her use of project-based learning (PjBL) to enhance students' speaking skills in grade 6 elementary students. The study centers on a single participant, exploring her insights and strategies through in-depth semi-structured interviews complemented by analysis of her daily reflective journals. These methodologies provide a comprehensive view of her ongoing pedagogical adaptations and the personal reflections shaping her teaching approach. The main objective is to assess the effectiveness of reflective practices in implementing PjBL within English language classrooms, particularly in terms of improving students' speaking skills at grade 6 students. Second, how the PjBL can enhance speaking skills. The findings showed that reflective practice during PjBL implementation was effective to know students’ engagement, the increasing of critical thinking and creativity, teacher’s feedback and challenges and solutions. It was also found that PjBL can promote speaking skills through the authentic communication among the members and collaborative works, increasing vocabularies related to the project topics, and sufficient chance to boost confidence to practice speaking. Keywords: Elementary, PjBL, speaking skill, teacher’s reflection